MODERASI PERTUMBUHAN PERUSAHAAN DIANTARA PENGARUH MANAJEMEN MODAL KERJA TERHADAP PROFITABILITAS PADA PERUSAHAAN TERINDEKS LQ45 DI BURSA EFEK INDONESIA - Gita Rahayu; Edyanus Herman Halim; Kamaliah Kamaliah (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The information that is often needed by investors is about the company's ability to generate profits which is calculated using the profitability ratio. profitability is the most important determinant of profitability because the main indicator of a company's ability to pay dividends is the company's ability to generate profits. In addition to analyzing profitability ratios, investors also need to consider share ownership by directors or commissioners of the company. This study aims to determine and analyze the effect of working capital turnover, inventory turnover and accounts receivable turnover on profitability. Knowing and analyzing working capital turnover, inventory turnover and accounts receivable turnover on profitability with company growth as a Moderating Variable. In this study, the population is Lq45 companies listed on the Indonesia Stock Exchange in 2016-2020. From the total population, the sample is determined as many as 40 companies. The data used in this study are primary data and secondary data, while the technique of collecting data on the company's financial statements. Data analysis techniques in this research use 2 data analysis methods, namely multiple regression and Moderated Regression Analysis (MRA). Based on the findings of working capital turnover, inventory turnover and accounts receivable turnover have a significant effect on profitability. Company growth is able to moderate the effect of working capital turnover, inventory turnover and accounts receivable turnover on profitability,